Refractory urticaria and the importance of diagnosing Schnitzler's syndrome. Issue 4 (29th April 2019) - Nham, Tina; Saleh, Carol; Chu, Derek; Vakaljan, Stephanie L; Ohayon, Jason A; Siegal, Deborah M
Abstract : A 52-year-old man presented with chronic urticaria that was refractory to standard chronic spontaneous urticaria (CSU) treatment. Over time, he developed systemic symptoms including fatigue, weight loss, arthralgia and bone pain. His laboratory investigations also became significant for microcytic anaemia, neutrophilia and elevated C reactive protein, erythrocyte sedimentation rate and IgE levels, in addition to an IgM monoclonal protein. He achieved only partial remission with typical medications for CSU including omalizumab, cyclosporine and cetirizine. After 6 years, his worsening symptoms and abnormal investigations led to a rare diagnosis of Schnitzler's syndrome and a trial of the interleukin 1 receptor antagonist, anakinra, which caused a rapid and complete resolution of his symptoms.